Reverse Logistics Strategies and Their Effect on the Competitiveness of Fast-Moving Consumer Goods Firms in South Africa - Mpho Sharon Makgedi Makaleng; Progress Hove-Sibanda (Logistics)
Background: The fast-moving consumer goods (FMCG) sector contributes significantly to the gross domestic product (GDP) growth of a country. This has therefore led to the growth in importance of reverse logistics (RL) since the FMCG sector cannot avoid RL. It is therefore important for the sector to implement RL strategies that can lead to firm competitiveness. Through the implementation of RL strategies, this sector will achieve many goals as well as lead to firm competitiveness. This study mainly sought to investigate RL strategies and their effect on firm competitiveness. Methods: A positivist research philosophy was employed. Data were collected through two close-ended questionnaires via SurveyMonkey from 418 FMCG retailers and consumers. This is because customers and employees are the greatest asset for any sector. Results: The descriptive results revealed the following RL strategies as the highly implemented ones among FMCG retailers: integration of forward logistics (FL) and RL, the implementation of new technology, the adherence to environmental policies and regulations, knowledge management, eco-compatibility and strategic alliances. The structural equation modeling (SEM) analysis revealed that RL strategies have a positive and significant influence on firm competitiveness. Conclusion: The results offer insight into the RL strategies that must be carried out to achieve firm competitiveness.